Pengaruh Islamic Human Development Index (I-HDI), Inflasi, dan Bantuan Sosial Pemerintah terhadap Kemiskinan di Indonesia Tahun 2019-2023 - Maisyahrani, Maisyahrani (Faculty of Economics and Business, 2025)
This study aims to examine the influence of the Islamic Human Development Index (I-HDI), inflation, and government social assistance on poverty in Indonesia from 2019 to 2023. A panel data regression method with a quantitive approach was used used and processed using the E- Views 12. The results show that all three variables have a significant negative effect on poverty. These findings are consistent with those of Rehman et al., (2022) and Kunjtorowati et al., (2024), but contrast with Agustin & Sumarsono, (2022), who found that social assistance had not been effective. This research highlights the importance of Islamic value-based development, effective inflation control, and well-targeted social programs as sustainable strategies for poverty alleviation.